Spray forming of Si-Al alloys for thermal management applications - Lambourne, A (2007)
This thesis describes the processing and characterisation of Al-70Si alloys manufactured by gas atomised spray forming at Sandvik-Osprey (Neath, UK) and Oxford University using a newly commissioned spray forming pilot-plant facility. Spray formed Al-70Si (CE7) provides an attractive balance of thermophysical properties making it suitable for thermal management applications. Microstructural characterisation of CE7 was conducted using optical microscopy, image analysis, electron probe micro analysis (EPMA) and electron backscatter diffraction (EBSD). Microscopy revealed an interpenetrating network microstructure consisting of fine, randomly oriented polycrystalline primary Si interpenetrated by large, α-Al grains devoid of eutectic Si. Mechanical testing and thermal cycling simulated a service environment and revealed for the first time crack initiation, growth and blunting mechanisms, the effect of intermetallic phases on the bulk mechanical properties, and anisotropy effects resulting from macrosegregation of Al during solidification. A relationship between the inter-phase interface length and the fracture toughness has been proposed and methods of interface length refinement have been investigated, including chill casting and spray forming. Spray formed CE7 modified with separate additions of B, P, P+Ce and Sr have been microstructurally and mechanically characterised and compared with binary CE7. While alloy additions were effective in refining primary and eutectic Si in chill cast alloys, spray formed alloys showed little change in interface length. Particle injection of Si-Al powder was effective in refining the scale of the spray formed microstructure, and improving mechanical properties. The deleterious effect of intermetallic phases on bulk mechanical properties has been demonstrated and highlighted the importance of melt cleanliness and materials control during manufacturing.